PERBANDINGAN PENINGKATAN FAKTOR PEROLEHAN MINYAK ANTARA POLA INJEKSI TUJUH TITIK DENGAN POLA MODIFIKASI TUJUH TITIK PADA SURFACTANT FLOODING - Ivan, Timothy
Recovery factor is one of the most important thing in oil and gas industry. Enhance Oil Recovery (EOR) method is used to increase the recovery factor. This method must be optimized before applied to oil field. This study was aimed to compare the recovery factor between seven-spot injection pattern and modified seven-spot injection pattern in surfactant flooding. These two mechanisms are used after the reservoir is produced by water flooding mechanism. After that, optimization is applied on the method which had the best recovery factor. This optimization is done by changing the parameters that may change the price of oil recovery factor. Beside that, this study also performed the simulation with the parameters that have been tested on a reservoir model with field scale. This study was conducted with a simulation model of artificial seven-spot injection pattern with Petrel RE simulator program. The study results showed that recovery factor from modified seven-spot mechanism was higher than seven-spot mechanism. Recovery factor of water flooding in modified seven-spot mechanism could reach 19% while the seven-spot mechanism was only reach about 10%.